Efektivitas Pelayanan Kesehatan Bagi Peserta BPJS di Puskesmas Kalirungkut - Hardianti Aniq, Azka; Shahira, Sharifah; Fitriana, Lilis; Anisykurlillah, Rosyidatuzzahro (VISA: Journal of Vision and Ideas, 2024)
This research aims to describe and analyze in depth the effectiveness of health services provided to BPJS participants at the Kalirungkut Community Health Center. The research method used was descriptive qualitative with an interview and observation approach to BPJS participants. The research results show that health services at the Kalirungkut Community Health Center have met the effectiveness indicators developed by Sutrisno (2007), namely program understanding, right on target, on time, achievement of goals, and real change. BPJS participants generally have a good understanding of the BPJS program, membership requirements and referral system, although understanding of the program's objectives still needs to be improved. The services at the Kalirungkut Community Health Center were assessed as being on target by participants, with high satisfaction with the facilities and services provided. Timely service processes and achievement of program objectives are reflected in the satisfaction of BPJS participants who experience direct benefits from this program. Apart from that, there have been positive changes in the attitudes and behavior of health workers who are now friendlier and more responsive to patient complaints. Several challenges such as officer delays are still encountered, but overall, the BPJS program at the Kalirungkut Community Health Center has succeeded in having a positive impact and fulfilling its main objective of providing adequate health insurance for the community. To increase the effectiveness of services, it is recommended that the Kalirungkut Community Health Center maximize socialization activities for the BPJS Program through Family Posyandu activities, increasing the function of monitoring and evaluating the performance of employees, especially front office employees.